Agreement On Settling The Flight Informtion Region (FIR) Boundary Line Between Indonesia And Singapore On Indonesia's Southernmost Island - Lenny Husna; Ukas Ukas (International Journal of Social Welfare and Family Law, 2025)
The goal of this research is to determine how the legal position of Singapore returning Flight Information Region (FIR) over the Riau Islands is founded on international law, which is the basis for delegating authority to Singapore to manage FIR over the Riau Islands. International legal recognition of sovereignty in airspace is contained in Article 1 of the 1919 Paris Convention, which states that "The contracting States recognize that every state has complete and exclusive sovereignty over the airspace above its territory". Indonesia has the authority to manage the airspace, which is divided into two Flight Information Regions (FIR), which are managed by two air traffic service centers, the Jakarta Air Traffic Service Center for the Jakarta FIR, which covers an area of 2,593,150 km2, and the Makassar Air Traffic Service Center for the Ujung Pandang FIR, which covers an area of 4,946,543 km2. Yet, the management of FIR in these areas has never been within the control of the domestic government since Indonesia's independence. Based on international law, a judicial examination was conducted to examine Indonesia's agreement with Singapore over the takeover of the airspace service or flight information region (FIR) over the Riau Archipelago area. According to the research findings, certain articles in the FIR Agreement are quite burdensome to Indonesia. And this agreement must be thoroughly examined to determine whether it favors Indonesia or vice versa.